Vietnam’s National Export Strategy: Evidence from an Economic Policy Modelling Study - Hoa, Tran Van; Vu, Jo; Thanh, Ho Trung (Thammasat Review of Economic and Social Policy, 2021)
This paper is a rigorous study of Vietnam’s exports determination and its causal relationship to the country’s growth, and addresses growing concerns regarding Vietnam’s growth path. The objective is to provide substantive evidence and credible inputs from a demand-side macroeconomic perspective. Significantly for Vietnam, an important open and transition economy in Asia, the study is carried out from an economic integration growth framework. Specifically, a multi-simultaneous equation model of Vietnam’s endogenous growth and exports determination is developed. The model innovatively incorporates gravity theory and classical consumer demand contributors, Ironmonger-Lancaster new commodity attributes and Johansen policy impact add- and sub-factors (i.e., reforms and crises) explicitly in its economic integration structure. Empirical findings also provide significant evidence to support a focus on strategies affected by external or demand side determinants of Vietnam’s exports and the influence of crises and reforms. The research will contribute to advances in the international trade literature and the findings provide useful insights and much needed evidence-based inputs on the determination and contributors of Vietnam’s exports to the national economy. These strategic recommendations are useful to key stake-holders such as policy-makers, government and academic researchers, and business analysts for national export strategic policy analysis and practical implementation.